Effect of friction stir processed microstructure on tensile properties of an Al-Zn-Mg-Sc alloy upon subsequent aging heat treatment. Issue 1 (January 2018) - Charit, Indrajit; Mishra, Rajiv S.
Abstract: An as-cast Al-Zn-Mg-Sc alloy was friction stir processed varying tool related parameters, yielding microstructures with different grain sizes (0.68, 1.8 and 5.5 μm). Significant increases in room temperature ductility were obtained in these materials with reasonable enhancement in strength. It is demonstrated that the type of microstructure produced by friction stir processing (FSP) has a significant influence on the choice of post-FSP heat treatment design for achieving improved tensile properties. It is also found that the ultrafine grained FSP material could not achieve the desired high strength during the post-FSP heat treatment without grain coarsening, whereas the micro-grained FSP materials could reach such strength levels (>560 MPa) under conventional age hardening heat treatment conditions.